SARS-COV-2 in Ophthalmology: Current Evidence and Standards for Clinical Practice - Torres-Costa, Sónia (2020)
Introduction: COVID-19 is caused by the coronavirus SARS-CoV-2. Ocular manifestations have been reported including conjunctivitis and retinal changes. Therefore, it is of the utmost importance to clarify eye involvement in COVID-19 in order to help with its diagnosis and to further prevent its transmission. The purpose of this review is to describe the structure and transmission of SARS-CoV-2, reported ocular findings and protection strategies for ophthalmologists.Material and Methods: Literature search on PubMed for relevant articles using the keywords ‘COVID-19’, ‘coronavirus’, and ‘SARS-CoV-2’ in conjunction with ‘ophthalmology’ and ‘eye’. Moreover, official recommendations of ophthalmological societies were reviewed.Results: Although the conjunctiva is directly exposed to extraocular pathogens, and the mucosa of the ocular surface and upper respiratory tract are connected by the nasolacrimal duct, the eye is rarely involved in human SARS-CoV-2 infection and the SARS-CoV-2 RNA positive rate by RT-PCR test in tears and conjunctival secretions from patients with COVID-19 is also extremely low.Discussion: The eye can be affected by SARS-CoV-2, which is supported by some reports of conjunctivitis and retinal changes, but its role in the spread of the disease is still unknown.Conclusion: Given the current scarce evidence, more research is needed to clarify the relationship between SARS-CoV-2 and the eye.